2020
DOI: 10.3390/s20092555
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fiber Sensors Based on Microstructured Optical Fibers to Detect Gases and Volatile Organic Compounds—A Review

Abstract: Since the first publications related to microstructured optical fibers (MOFs), the development of optical fiber sensors (OFS) based on them has attracted the interest of many research groups because of the market niches that can take advantage of their specific features. Due to their unique structure based on a certain distribution of air holes, MOFs are especially useful for sensing applications: on one hand, the increased coupling of guided modes into the cladding or the holes enhances significantly the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…The last generation FOCS sensors use the combination of surface plasmon resonance (SPR) sensing platform on plastic optical fibers (POFs), or use photonic crystal fibers (PCF). In addition, micro-structured optical fibers (MOFs), having a certain distribution of air holes in their structure, have been actively used recently for sensing applications for detecting liquids, gases, or volatile organic compounds (VOCs) [ 99 ].…”
Section: Other Types Of Optical Sensors For Popsmentioning
confidence: 99%
“…The last generation FOCS sensors use the combination of surface plasmon resonance (SPR) sensing platform on plastic optical fibers (POFs), or use photonic crystal fibers (PCF). In addition, micro-structured optical fibers (MOFs), having a certain distribution of air holes in their structure, have been actively used recently for sensing applications for detecting liquids, gases, or volatile organic compounds (VOCs) [ 99 ].…”
Section: Other Types Of Optical Sensors For Popsmentioning
confidence: 99%
“…The optical fiber sensor is based on the refractive index sensing principle, which has the significant advantage of immunity to electromagnetic interference compared to electronic or electrical sensors. [38][39][40] At the same time, real-time and remote sensing can be achieved with the benefit of advanced optical fiber sensing networks. 41 In optical fibers, the different modes of light are orthogonal and do not interfere with each other.…”
Section: Design and Simulation Of Lpfg Sensorsmentioning
confidence: 99%
“…Various types of NH 3 sensors have been reported during the last decades [ 5 , 6 , 7 ]. Among them, due to the merits of small size, resistance to electromagnetic interference, and high sensitivity [ 8 ], optical fiber sensors have been widely studied in the field of gas sensing [ 9 , 10 , 11 , 12 ]. For instance, Xu et al [ 13 ] reported a highly sensitive NH 3 sensor by coating graphene oxide (GO)/cellulose acetate (CA) on the surface of a long-period fiber grating (LPFG).…”
Section: Introductionmentioning
confidence: 99%